Pemanfaatan Jahe dan Pengolahannya untuk Kesehatan di SMA 1 pantai Cermin Surian - Kamal, Sefrianita; Serdiani, Serdiani; Nofrizal, Nofrizal; Dwinatrana, Khiky; Azzahra, Rafifa; Anggia, Malse; Fitri, Widya; Sari, Dian Permata; Azura, Faradila; Cahyani, Dinda; Fajriani, Susi (LPPM Universitas Dharma Andalas, 2025)
Plants from the Zingiberaceae family are the most commonly used in traditional medicine in Indonesia. Although modern medicine is rapidly developing in Indonesia, traditional medicine is still very often used in villages and cities. The part of the plant in the family member of the Zingiberaceae that is often used is its rhizoma which is distinctively aromatic and contains evaporated oil. This ginger has a lot of benefits, especially for health. Its antioxidant content can protect the body from free radicals and cell malignancy. Information about the benefits of this ginger plant was conveyed to the State High School 1 Pantai Cermin Surian, Solok Regency. This ginger plant can also be processed into an instant drink of ginger powder, On a visit to this school, a demonstration of making instant ginger was also carried out. It is hoped that through this service, students at SMA 1 Pantai Cermin can find out the benefits and how to process ginger.